Development of multi-epitope peptide-based vaccines against SARS-CoV-2 - Lim, Hui Xuan *; Lim, Jian Hua *; Jazayeri, S. D. *; Poppema, Sibrandes *; Poh, Chit Laa * (Elsevier, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a pandemic involving so far more than 15 million infections and 630,211 deaths. Effective vaccines are urgently needed to prevent SARS-CoV-2 infections. No vaccines have yet been approved for licensure by regulatory agencies. Even though host immune responses to SARS-CoV-2 infections are beginning to be unravelled, effective clearance of virus will depend on both humoral and cellular immunity. Additionally, the presence of Spike (S)-glycoprotein reactive CD4+ T-cells in the majority of convalescent patients is consistent with its significant role in stimulating B and CD8+ T-cells. The search for immunodominant epitopes relies on experimental evaluation of peptides representing the epitopes from overlapping peptide libraries which can be costly and labor-intensive. Recent advancements in B- and T-cell epitope predictions by bioinformatic analysis have led to epitope identifications. Assessing which peptide epitope can induce potent neutralizing antibodies and robust T-cell responses is a prerequisite for the selection of effective epitopes to be incorporated in peptide-based vaccines. This review discusses the roles of B- and T-cells in SARS-CoV-2 infections and experimental validations for the selection of B-, CD4+ and CD8+ T-cell epitopes which could lead to the construction of a multi-epitope peptide vaccine. Peptide-based vaccines are known for their low immunogenicity which could be overcome by incorporating immunostimulatory adjuvants and nanoparticles such as Poly Lactic-co-Glycolic Acid (PLGA) or chitosan.